Study of stability and interference for catecholamines and metanephrines, 3-methoxytyramine: key point of an accurate diagnosis for pheochromocytoma and paraganglioma. (2nd November 2021) - Wang, Kaijuan; Gao, Xiaojing; Zhang, Wei; Sun, Nian; Xie, Lan; Cong, Hongying; Guo, Yutong; Shi, Xiaocui; Zhou, Zhou
Abstract: Background: Accurate diagnosis of pheochromocytoma and paraganglioma (PPGLs) is highly dependent on the detection of metanephrines and catecholamines. However, the systematic investigation on influencing factors including specimen (plasma or whole blood), anticoagulant, storage conditions, and interference factors need further confirmation. Methods: Blood with heparin-lithium or EDTA-K2 were collected, stability of epinephrine (EPI), norepinephrine (NE), dopamine (DA), metanephrine (MN), normetanephrine (NMN), 3-methoxytyramine (3-MT) in whole blood and plasma at room temperature and 4 °C for different storage times, stability of plasma MN, NMN and 3-MT at −20 °C and −80 °C were investigated. Plasma with hemoglobin (1 g/L, 2 g/L, 3 g/L, 4 g/L, 6 g/L), TG (<5 mmol/L, 5–8 mmol/L, >8 mmol/L) were prepared. Results: EPI, NE, DA were prone to degrade at room temperature, samples should be centrifuged at 4 °C. EPI and NE were stable in whole blood at 4 °C for 4 h and in plasma for 2 h. For MN, NMN, 3-MT, plasma can be stable at room temperature and 4 °C for at least 6 h, which is better than whole blood; there was no significant difference when stored at −20 °C and −80 °C for 7 days. Heparin-lithium had a slight advantage over EDTA-K2. EPI, NE, DA should not be performed when Hb > 1 g/L or TG > 5 mmol/L. MN, NMN, 3-MT should not be performed when Hb > 2 g/L, whereas TG had no interference. Conclusions: According to the actual clinical application scenario, this study provided a reliable basis for the accurate diagnosis of PPGLs.